2002
DOI: 10.1002/jtra.1054
|View full text |Cite
|
Sign up to set email alerts
|

Further studies on the interrelationship of aluminum and silicon in patients receiving aluminum hydroxide therapy for dyspepsia and factors that relate to the solubilization of aluminum

Abstract: It is known that the intake of aluminum-containing antacids is related to increases in serum concentration and the urinary output of aluminum, and that silicon intake as orthosilicic acid may facilitate renal excretion of aluminum. However, how either the amount of antacid ingested or the therapy period affects these and the subsequent interrelationship of aluminum and silicon has not been fully investigated. In addition, factors that affect the solubility of aluminum hydroxide need further clarification. A st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…In addition, it is suggested that silicon intakes, as orthosilicic acid, may facilitate the renal excretion of aluminium. 170 Consequently, the co-ingestion of silicon with aluminium may both reduce aluminium bioavailability by the formation of insoluble aluminosilicate complexes within the gut contents and increase the rate of excretion of that aluminium which crosses the gut barrier. Using the same methods an excess 26 Al uptake was seen in Down's syndrome patients, compared with controls and a 1.6 times excess 26 Al uptake has been described in Alzheimer's patients compared with age-matched controls.…”
Section: Bioavailability Studies Using 26 Almentioning
confidence: 99%
“…In addition, it is suggested that silicon intakes, as orthosilicic acid, may facilitate the renal excretion of aluminium. 170 Consequently, the co-ingestion of silicon with aluminium may both reduce aluminium bioavailability by the formation of insoluble aluminosilicate complexes within the gut contents and increase the rate of excretion of that aluminium which crosses the gut barrier. Using the same methods an excess 26 Al uptake was seen in Down's syndrome patients, compared with controls and a 1.6 times excess 26 Al uptake has been described in Alzheimer's patients compared with age-matched controls.…”
Section: Bioavailability Studies Using 26 Almentioning
confidence: 99%
“…However, this element, in fact, negatively impacts human health (Osinska et al, 2004). It is present in many manufactured foods (Abbasali et al, 2005) and pharmaceutical products (Roberts et al, 2002).…”
mentioning
confidence: 99%